Take away - Cheng, Clara Boon Ruan (Nanyang Technological University, 2021)
Living standards in urbanised cities, such as Singapore, are prone to be quick-paced and transitory. Thus, lesser opportunities are present to foster intimacy in settings involving family and friends. Take Away is a board game that aims to reconnect already existing relations, or create new ones, through reflective, purpose driven cards centred around the topic of food. Often, food itself can forge a bridge between two separate individuals. This can be done, through a conversation over a meal, or a banter over cuisine favourites. The game implements various food-themed conversation starters that allow players to deepen their understanding of one another through motions of the game. Take Away hopes to take fostering intimacy a step further, by pre-empting cooking as an activity through its end intention of customised recipes, unique to the game’s players.